(3QhVI GdeTJGb hHgLI GdYTGbs - (3eGejG GdQhej, eMeO CMeO Hf YHO Gddg, J (B988(3g`s
(3ChdgG (B:s
(3GdMeO ddg MeO ef GHJcQ YQGFS CHcGQ GdCacGQ aj HjhJ GdfXGe hGSJNOe dgG QbGFb CLfGS GdLfGS adHJ WGFYI ddGSJNOGes
(3BNQgG (B:s
(3hTgQ ThGd GdQVG gd haj (B*** (3JGQjNg JgfFI HGdYjOs
(3LGA aj BNQ CHjGJ GdOjhGf JGQjN bO jchf JGQjN JHjjV GdeDda dOjhGfg Ch ZjQ Pdc, hGdJGQjN gh SfI (B983(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 7s
(3eYLe GdeDdajf(B: 3 / 75s
(3EjVGM Gdecfhf(B: 1 / 491s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs